Effective Tax Rates and Effective Progressivity in a Fiscally Decentralized Country - Marcus Roller; Kurt Schmidheiny (Center for Economic Studies and ifo Institute (CESifo), 2016)
This paper proposes measures to quantify the effective level and the effective progressivity of taxation in a fiscally decentralized country taking income sorting into account. Using data on the universe of Swiss taxpayers, we find that rich households effectively face significantly lower average and marginal tax rates and lower progressivity than in the benchmark case that does not consider income sorting. This is because high-income households systematically avoid high taxation by locating in low-tax jurisdictions. The results are stronger for singles than for families, indicating that singles are more sensitive to spatial tax differentials than families. Although income tax schedules of the Swiss federation, the 26 cantons and the more than 2,600 municipalities are all strictly progressive, the effectively paid country-wide average tax rate is regressive for households with very high incomes and without children. The proposed measure of the effective average and marginal tax rates also allows us to adequately describe the evolution of the country-wide tax burden over time. We document that about half of the reduction in the tax burden on top incomes between 1975 and 2009 is due to reductions in statutory tax rates and about half to stronger income sorting of the population. Our results also hold when we account for the disutility from housing prices into which tax rates capitalize.
Keywords: H71; H73; R23; 330; effective tax rates; progressive taxation; fiscal decentralization; income segregation